Effects of Enzymatically Depolymerized Low Molecular Weight Heparins on CCl4-Induced Liver Fibrosis - Yan, Yishu; Guan, Changge; Du, Shanshan; Zhu, Wenming; Ji, Yang; Su, Nan; Mei, Xiang; He, Dong; Lu, Yuan; Zhang, Chong; Xing, Xin-Hui (Frontiers in Pharmacology, 2017)
With regard to identifying the effective components of LMWH drugs curing hepatic fibrosis disease, we carried out a comparative study on the efficacy of enzymatically depolymerized LMWHs on CCl4 induced mouse liver fibrosis. The results showed that the controlled enzymatic depolymerization conditions resulted in LMWHs with significantly different activities. The LMWH product depolymerized by Heparinase I (I-11) with a Mw of 7160, exhibited a significant advantage in reducing the liver inflammation by suppressing TNF-α and IL-1β secretion, and minimizing hepatic fibrogenesis. The products prepared by only Heparinase II (II-11), and combined Heparinase III and II (III-II-5) showed limited positive effect on hepatic inflammation and fibrosis. On the contrary, the products by combined Heparinase III and I (III-I-9, III-I-5) showed no effect or stimulation effect on the hepatic fibrogenesis. Our results provided the basis for structure-activity relationship insight for inhibition of liver fibrosis activities of LMWHs, which might have significant implications for generic anti-fibrosis disease drug development.